Youth Labour Flows and Unemployment in Great Recession: Comparing Spain and the Czech Republic - Vladislav Flek; Martina Mysíková (Review of Economic Perspectives, 2015)
Using Spain and the Czech Republic as examples of two EU countries with different labour market performance, we apply a gross flow analysis based on EU-SILC longitudinal data. We find that while in Spain the increases in youth unemployment are driven mostly by young people who lose their jobs, in the Czech Republic, this is mainly due to new labour market entrants who failed to find a job. The analysis of flow transition rates suggests that youth labour markets with enormously high unemployment rates have not failed in all relevant respects. Their development seems to be hindered predominantly by high risk of job losses and diminishing employment prospects of the unemployed, rather than by impeded transitions from inactivity to employment. In countries with lower youth unemployment rates, unemployment policy agenda appears to be challenged by quite the opposite tendency
Keywords: 330